Extracción de arena para construcción y su efecto en suelo de altura en la ciudad de Requena Loreto-2019 - Zambrano Magalhaes, Leidi Corali (2021)
The present work you development in the city of Requena, department of Loreto the objective was of evaluating the extraction of sand for construction and its effect in a floor of height, the study was of descriptive type, the design was experimental descriptive correlacional, the population it was conformed by the existent quarries in activity and in abandonment in the city of Requena that according to sources (municipality of Requena), the sample conformed it the 6 quarries. being reached the following conclusions; in the social dimension 66,7% doesn't have operation license neither permission of transport of the material, with respect to the origin of the quarry 66,7% is public, with respect to the social conflict 50% affirms that before it existed now no longer; in the environmental dimension, 66,7% affirms that it is of low level, with regard to the erosion of the floor 83,3% says that it is high, 66,7% affirms that it affects the landscape, with respect to the noise that you/they carry out the trucks 66,7% he/she says that it is high, with respect to the contamination of the floor 83,3% says that it is high and 66,7% affirms that loss of the vegetation exists. with respect to the hypothesis outlined investigation work presently on the extraction of sand for construction and their effect in floor of height in the city of Requena. this is accepted.